FORMS OF FREEDOM IN NICOLÁS BRAVO’S THOUGHT. OF THE INDEPENDENCE CHALLENGE TO THE REPUBLICAN EPOCH. (Tzintzun, Revista de Estudios Históricos, 2016)
In the ideological universe of the 19th century, the word freedom, maintained somecomplexity and multiples meanings. The article analyzes the types of freedom manifestin the political speeches of the insurgent - republican Nicolás Bravo during thedifferent moments of his public life. This will allow contextualizar the relation betweenhis ideological principles and his interes personal. In the long process of training ofthe Mexican nation the transformation of the civil and political values did to evolvethe meaning of said term. The freedom was concebida as an expression of politicalindependence in opposition to the authority that was supporting the control, theoppression, the arbitrariness, the slavery and the despotism, also it was thoughtabout her, it associating with the republican regime, which was demanding the directand permanent participation of every citizen in the public matters. Together withthese two should appear more: one who was pleading for a moderate, freedomaristocratic and opposite to the excesses; and other one that was demanding theattachment irrestricto to the law.
Keywords: Nicolás Brav; freedom; Mexican independence; nationalism; republic